Magnetic contribution to electric resistance of gadolinium single crystal at low temperatures - Finkel, V.A.; Derevyanko, V.V. (Functional Materials, 2004)
Electrical resistance of a single crystal of ferromagnetic rare-earth metal, gadolinium, has been measured within 150 to 325 K temperature range including the Curie point Tc and the spin reorientation temperature Tsr. The temperature dependences of magnetic contribution to the electric resistance, (p/p)magn, along the main c axis and normal thereto are qualitatively different: along the c axis, this dependence has a convex curve shape while in the ab plane, it is a concave one showing a kink at Tsr. Измерено электросопротивление монокристалла ферромагнитного редкоземельного металла гадолиния в диапазоне температур 150-325 К, включающим точку Кюри Tc и температуру спиновой переориентации Tsr. Установлено, что температурная зависимость магнитного вклада в электросопротивление (Ap/p)magn вдоль главной оси c и в перпендикулярном направлении носит качественно различный характер - выпуклая кривая вдоль оси c и вогнутая кривая с резким перегибом в Tsr для плоскости ab. Виміряно електроопір монокристала феромагнітного рідкіснозємєльного металу гадолінію у діапазоні температур 150-325 K, який включає точку Кюрі Tc та температуру спінової переорієнтації T. Встановлено, що температурна залежність магнітного внеску у електроопір (Ap/p)magn вздовж головної вісі c та у перпендикулярному напряму має якісно різний характер - выпукла крива вздовж вісі c та угнута крива із різким перетином T для площини ab.